Constituent Postponement in Biblical Hebrew Verse - Redd, John Scott (Abhandlungen für die Kunde des Morgenlandes, 2014)
Cover; Title Page; Copyright; Table of Contents; List of Tables; List of Abbreviations; Linguistic Abbreviations; Preface; Body; 1 Introduction; The Present Interest; Poetry and Prose; Formal Defamiliarization; 2 Classical Biblical Hebrew Prose; Distinct Phases in Biblical Hebrew; Word Order in Classical Biblical Hebrew; 3 Preverbal Constituents in BH Prose; Introduction; Two Preverbal Constituents in BH Prose; Previous Analysis: Word Order Studies; Word Order Studies in Verse; Rosenbaum (1997); Gross (1996, 2001); Lunn (2006); Complements and Adjuncts; Corpus; 4 Verbal Postponement.